Desa Senawar Jaya 1992-2011 - Mistiawati, Mistiawati; Azmi, Ulul; Yanto, Ferry (Universitas Batanghari Jambi, 2024)
This research aims to explain the history of the establishment of Senawar Jaya Village and understand the social conditions of Senawar Jaya Village. The research method used is the historical method, following systematic principles in collecting historical sources. The research stages include the collection of heuristic sources, criticism, interpretation, historiography, and interviews to complement the obtained data.The theory used in this research is the bottom-up and top-down village development theory by Shabbir Cheema and Dennis Rondinelli, which states that both the central and local governments make efforts to encourage development. The research findings indicate significant progress in the development of Senawar Jaya Village, although it took a considerable amount of time. This village development also involved various parties, such as the central and local governments, as well as the residents of Senawar Jaya Village, and had an impact on the village’s inhabitants.